Quetiapine for acute bipolar depression: A systematic review and meta-analysis - Sirijit Suttajit (2018)
Background: Precise estimated risks and benefits of quetiapine for acute bipolar depression are needed for clinical practice. Objective: To systematically review the efficacy and the tolerability of quetiapine, either as monotherapy or combination therapy, for acute bipolar depression. Methods: We included all randomized, controlled trials (RCTs) comparing quetiapine with other treatments, including placebo, in patients with acute bipolar depression (bipolar I or II disorder, major depressive episode). Published and unpublished RCTs were identified using the Cochrane Central Register of Controlled Trials, MEDLINE®, Web of Knowledge™, CINAHL®, PsycINFO®, the EU Clinical Trials Register database, and ClinicalTrials.gov. The primary outcome was the change scores of depression rating scales. Results: Eleven RCTs (n=3,488) were included. Two of them were conducted in children and adolescents. The change in depression scores was significantly greater in the quetiapine group compared with the placebo group (mean difference, [MD] =-4.66, 95% confidence interval [CI] -5.59 to -3.73). The significant difference was observed from week 1. Compared with placebo, quetiapine had higher incidence rates of extrapyramidal side effects, sedation, somnolence, dizziness, fatigue, constipation, dry mouth, increased appetite, and weight gain but lower risks of treatment-emergent mania and headache. Quetiapine treatment was associated with significant improvement of clinical global impression, quality of life, sleep quality, anxiety, and functioning. Conclusion: Quetiapine monotherapy is effective for acute bipolar depression and the prevention of mania/hypomania switching. Its common adverse effects are extrapyramidal side effects, sedation, somnolence, dizziness, fatigue, constipation, dry mouth, increased appetite, and weight gain. The lower risk of headache in quetiapine-treated patients with acute bipolar depression should be further investigated. The evidence for the use of quetiapine combined with mood stabilizers in children and adolescents with acute bipolar depression is too small to support the clinical practice. © 2014 Suttajit et al.